Modelo biomecânico de punho para a simulação computacional de tremores patológicos em malha fechada utilizando Controle H∞ - Pinheiro, Wellington Cássio. (2019)
In the last decades, the world’s been through an expressive raise in life expectancy and consequently increasing age-related diseases such as pathological tremor. Assistive technology development may be benefited by individualized mathematical models capable of reproducing affected limb behavior. This work aims to develop a biomechanical model of pathological tremor, using realistic musculoskeletal representations to serve as a plant for testing suppression strategies. In order, a MATLAB forward dynamics interface was implemented allowing the use of modeling and closed-loop control techniques to reproduce, in a statistical manner, the pathological tremor observed on an individual. As a result, a two degree-of-freedom biomechanical model of pathological tremor was obtained, which successfully reproduces tremor kinematics as well as tremor frequency and its variability with K-L divergence of 1 × 10−7.